Pengaruh Struktur Organisasi Terhadap Inovasi Perusahaan PT. Bank BRI Syariah Kantor Cabang Banjarmasin - Riska Maulida Anggraini; Saladin Ghalib (JURNAL BISNIS DAN PEMBANGUNAN, 2023)
The purpose of this study was to determine the effect of organizational structure on innovation at the branch office of PT. BRI Syariah Banjarmasin. Innovation is recognized as one of the keys to success in an organization, but an innovation will not run well if there is no regulation from the organization, so that innovation is closely related to organizational structure. The variable used in this study is the organizational structure with 3 dimensions: complexity, formalization, and centralization, while the innovation variable has 2 dimensions: the initiation stage and the implementation stage. This study uses a quantitative approach with a total sample of 100 employees of BRIsyariah Banjarmasin. Data collection techniques used primary and secondary data, and were analyzed using the Amos 22 SEM application. Based on the results of the analysis, it was found that complexity had a partial and significant effect on initiation, complexity had no partial and significant effect on implementation, formalization had a partial and significant effect on the initiation stage. , formalization does not have a partial and significant effect on implementation, centralization has a partial and significant effect on initiation and centralization has a partial and significant effect on implementation Keywords: Organizational structure, innovation, complexity, formalization, initiation, implementation